Statins Induce Actin Cytoskeleton Disassembly and an Apoptosis-Like Process in Acanthamoeba spp. - Rubén L. Rodríguez-Expósito; Ines Sifaoui; María Reyes-Batlle; Sutherland K. Maciver; José E. Piñero; Jacob Lorenzo-Morales (MDPI AG, 2022)
Acanthamoeba is a ubiquitous opportunistic protozoan pathogen that is known to cause blinding keratitis and rare, but usually fatal, granulomatous encephalitis. The difficulty in treating infections and the toxicity issues of the current treatments emphasize the need to use alternative agents with amoebicidal activity. The aim of this study was to evaluate the in vitro antiamoebic activity of three third-generation statins-cerivastatin, pitavastatin and rosuvastatin-against both cysts and trophozoites of the following four strains of Acanthamoeba: A. castellanii Neff, A. polyphaga, A. griffini and A. quina. Furthermore, programmed cell death (PCD) induction traits were evaluated by measuring chromatin condensation, damages at the mitochondrial level, production of reactive oxygen species (ROS) and the distribution of actin cytoskeleton fibers. Acanthamoeba castellanii Neff was the strain most sensitive to all the statins, where cerivastatin showed the lowest amoebicidal activity for both trophozoite and cyst forms (0.114 ± 0.050 and 0.704 ± 0.129 µM, respectively). All the statins were able to cause DNA condensation, collapse in the mitochondrial membrane potential and a reduction in ATP level production, and disorganization of the total actin fibers in the cytoskeleton of all the evaluated Acanthamoeba strains. Our results showed that the tested statins were able to induce PCD compatible events in the treated amoebae, including chromatin condensation, collapse in the mitochondrial potential and ATP levels, cytoskeleton disassembly and ROS generation.